Aktivitas Sitotoksik Ekstrak Metanol Benalu Batu (Begonia sp.): Ethnomedicine Suku Wana Sulawesi Tengah - MUHAMMAD SULAIMAN ZUBAIR; SYARIFUL ANAM; YULIET .; AGUS RITNA; FIRMANITA DWIMURTI; DEWI RISMAYANTI (Fakultas Farmasi Universitas Pancasila, 2014)
Benalu batu (Begonia sp.) is used as traditional medicine by Wana tribe in Central Sulawesi to treat various diseases, including cancer. In an effort to search potential anticancer drugs from natural sources, investigation was conducted on the cytotoxic activity of Begonia sp. methanol extract against cervic cancer cells (HeLa) and breast cancer cells (T47D) and identification of the chemical compound groups in methanol extract that is responsible for the anticancer activity. Investigations including the extraction of Begonia sp. dried herb by soxhletation using methanol, followed by evaporation on rotary vapor until viscous extract gained. The cytotoxic test were carried out by tetrazolium bromide (MTT) method. The concentration series of Begonia sp. methanol extract were 250, 125, 62.5 and 31.25 μg /mL. Results showed that the Begonia sp. methanol extract inhibited the growth of cervic cancer cells (HeLa) (IC50 = 70.97 μg/mL) stronger than inhibition on breast cancer cells (T47D) (IC50 = 122.21 μg/mL). Analysis of chemical compound groups in the methanol extract using thin-layer chromatography (TLC) method indicated that polyphenolic flavonoid might be the main compound responsible for the anticancer activity